Hemodynamic changes during endotracheal intubation: A prospective randomised comparative study using fibreoptic bronchoscope and intubating laryngeal mask airway - Shrestha, Manzil; Rahman, Tanvir R; Agarwal, Bikash (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Fibreoptic intubation and Intubating laryngeal mask airway are alternatives to conventional laryngoscopy. The objective of the study was to compare hemodynamic changes with the use of these two devices for tracheal intubation. Methods: It was a randomized, comparative and prospective study of two groups comprising of 50 patients each. Tracheal intubations were performed using intubating fiberscope in group I and intubating laryngeal mask airway in Group II. Intubation time, heart rate, blood pressure and complications were compared. Results: Heart rate response to tracheal intubation was comparable between the groups. Changes in mean arterial pressure were also comparable and returned to baseline after two minutes of tracheal intubation. The first attempt success rate was 80% and 92% respectively in Group I and Group II. The time taken for intubation was found to be significantly longer in Group II irrespective of the number of attempts. There were no major complications observed. However there was some desaturation at the time of intubation which was seen in three patients in Group I, and one patient in Group II. However the Spo2 did not fall below 96% and was not considered to be clinically significant. Conclusions: Endotracheal intubation using either an Intubating Laryngeal Mask Airway or a Fibreoptic Bronchoscope is comparable in terms of the haemodynamic responses. Journal of Society of Anesthesiologists 2014 1(2): 70-75